PENGARUH JUMLAH PENDUDUK, DANA BAGI HASIL, DAN TOTAL BELANJA DAERAH TERHADAP INDEKS KESULITAN SOSIAL DI KOTA PEKANBARU - HAMID, M; NURFITRIANI, NURFITRIANI; SILKFAN, RARA; ADIMAN, RAJA MULTI KONVOKESEN (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
This study aims to analyze the effect of population, Revenue Sharing Fund (DBH), and total regional expenditure on the Social Difficulty Index (IKS) in Pekanbaru City during 2015–2023. Using an explanatory quantitative approach and multiple linear regression, the results show that partially, the population and total regional expenditure have a significant negative effect on the IKS, while DBH has a negative but insignificant effect. Simultaneously, these three variables explain 91% of the variation in IKS. These findings confirm that effective regional expenditure expansion and population growth accompanied by strong economic growth can reduce social difficulties, whereas optimization of DBH utilization still requires improvement.